New molecular phylogeny of Lucinidae: increased taxon base with focus on tropical Western Atlantic species (Mollusca: Bivalvia) - Taylor, John D.; Glover, Emily A.; Smith, Lisa; Ikebe, Chiho; Williams, Suzanne T. (Zootaxa, 2016)
A new molecular phylogeny of the Lucinidae using 18S and 28S rRNA and cytochrome b genes includes many species from the tropical Western Atlantic as well as additional taxa from the Indo-West Pacific. This study provides a phylogenetic framework for a new taxonomy of tropical Western Atlantic lucinids. The analysis confirmed five major clades—Pegophyseminae, Leucosphaerinae, Myrteinae, Codakiinae and Lucininae, with Monitilorinae and Fimbriinae represented by single species. The Leucosphaerinae are expanded and include Callucina winckworthi and the W. Atlantic Myrtina pristiphora that groups with several Indo-West Pacific Myrtina species. Within the Codakiinae two abundant species of Ctena from the Western Atlantic with similar shells are discriminated as C. orbiculata and C. imbricatula, while in the Indo-West Pacific Ctena bella is a probable species complex. The Lucininae is the most species rich and disparate subfamily with several subclades apparent. Three species of Lucina are recognized in the W. Atlantic L. aurantia, L. pensylvanica and L. roquesana. Pleurolucina groups near to Cavilinga and Lucina, while Lucinisca muricata is more closely related to the E. Pacific L. fenestrata than to the Atlantic L. nassula. A new species of Parvilucina is identified from molecular analyses having been confounded with Parvilucina pectinata but differs in ligament structure. Also, the former Parvilucina clenchi is more distant and assigned to Guyanella.